STUDI KASUS PROSES INERTING TANKI MUATAN PADA KAPAL MT. GAS WALIO DALAM RANGKA PERSIAPAN DOCKING - Teguh Purnomo; Nazarudin Sinaga; Nafi Almuzani (Dinamika : Jurnal Ilmiah Teknik Mesin, 2021)
In handling cargo, some types of ships have different ways. On gas tankers containing LPG, a special process is required in avoiding explosions in cargo tanks and avoiding the waste of cargo into the atmosphere. The process of handling the payload is the inerting porses on the payload tank. This process includes inert gas with oxygen levels of less than 8% to prevent the formation of fire triangles in the payload tank so as to avoid explosions. Inert gas is produced by an engine in the form of an Inert Gas Generator. Inert gas generators have several components, the process of which is interconnected with each other to produce inert gases. Inert gas generators require a good and correct maintenance and repair system considering the purpose of inserting inert gas into the payload tank is significant in terms of safety and security on board. Case study on board MT. Walio gas observes the activities of the inerting process that is disrupted by the waste of inert gas into the atmosphere and has a high dew point value so that inert gas does not enter the tank load. From the results of the case study intended that the components on the gas generator inert do not function properly, some analysis is done by observing the continuity of the process and written data so that it is expected that the case study has the benefit in theory and practice in handling the continuity of the inerting process.